2016
DOI: 10.1245/s10434-016-5246-8
|View full text |Cite
|
Sign up to set email alerts
|

How Often Does Neoadjuvant Chemotherapy Avoid Axillary Dissection in Patients With Histologically Confirmed Nodal Metastases? Results of a Prospective Study

Abstract: Background In breast cancer patients with nodal metastases at presentation, false-negative rates <10% have been demonstrated for sentinel node biopsy (SLNB) after neoadjuvant chemotherapy (NAC) when ≥3 negative sentinel nodes (SLNs) are retrieved, but the frequency with which axillary dissection (ALND) can be avoided is uncertain. Methods Among 534 prospectively identified consecutive patients with clinical stage II–III cancer receiving NAC from 11/2013–11/2015, all biopsy-proven node-positive (N+) cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
155
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(171 citation statements)
references
References 31 publications
14
155
1
1
Order By: Relevance
“…Only 2 of 6 primary ILC malignancies demonstrated a 100% reduction in 18 F-fluciclovine avidity, and both demonstrated a complete pathologic response. ILC is known to have a lower rate of a pathologic complete response after neoadjuvant therapy than IDC, although this pattern may be secondary to ILC tumors more commonly expressing ER1/HER22 receptor status, a phenotype that has a lower rate of a pathologic complete response (29,30). This pattern appeared in our small dataset.…”
Section: Discussionmentioning
confidence: 73%
“…Only 2 of 6 primary ILC malignancies demonstrated a 100% reduction in 18 F-fluciclovine avidity, and both demonstrated a complete pathologic response. ILC is known to have a lower rate of a pathologic complete response after neoadjuvant therapy than IDC, although this pattern may be secondary to ILC tumors more commonly expressing ER1/HER22 receptor status, a phenotype that has a lower rate of a pathologic complete response (29,30). This pattern appeared in our small dataset.…”
Section: Discussionmentioning
confidence: 73%
“…hot and/or blue nodes, and must not be randomly sampled. Mamtani et al [16] investigated patients with histologically proven node-positive disease who underwent NACT; 68.0% turned clinically node-negative and were eligible for SLNB. Of 128 SLNB attempts, ≥3 sentinels were identified in 86.0%, and 48.0% were histologically node-negative and spared an ALND.…”
Section: Clinically Node-positive Patients Prior To Nactmentioning
confidence: 99%
“…Hormone receptor-positive patients are less likely to achieve pCR than those with triple-negative or human epidermal growth factor receptor 2 (HER2)-positive breast cancer, highlighting the importance of patient selection. [15,16] With the addition of targeted therapy in HER2-positive patients, the conversion rates have increased to >70%. [18] Besides the prognostic implications of evaluating response, the use of NACT has the attractive potential to increase axilla-preserving surgical therapy by reducing the need for ALND in patients who are node-negative after NACT.…”
mentioning
confidence: 99%
“…It must be remembered that the main objective of preoperative chemotherapy, apart for guaranteeing the possibility of BCT, is to avoid axillary lymphadenectomy. A few studies have shown that the pCR rate within the lymph nodes after preoperative chemotherapy, especially in the following phenotypes: triple--negative and HER2-positive, amounts to 40-50% [16][17][18] (Tab. I).…”
Section: Preoperative Chemotherapy In the Patients At The N+ Clinicalmentioning
confidence: 99%
“…I). What is important, axillary lymphadenectomy may be avoided in about 50% of patients with SLN biopsy, confirmed with pCR, after pre-operative chemotherapy especially that the majority of them, an account of the baseline metastatic involvement of the axillary lymph nodes, will undergo radiotherapy of the nodal fields [8,[16][17][18] (www.oncoconferences.ch/BCC). This fits to the generally accepted tendency to limit axillary lymphadenectomies in breast cancer patients [www.oncoconferences.ch/BCC].…”
Section: Preoperative Chemotherapy In the Patients At The N+ Clinicalmentioning
confidence: 99%